Financial Cointegration and the Vector Error Correction Model: The Case of MENA Countries - Lamia, Kalai; Naziha, Kasraoui (International Journal of Economics and Financial Issues, 2019)
The aim of this paper is to study financial integration between emerging MENA countries and developed countries. We study short-term price series dynamics using Johansen's (1991) multivariate cointegration test to determine the number of cointegration vectors and Granger's (1987) causality test to determine causality direction across markets. The VECM model combines long-term cointegration modeling with short-term dynamics to determine equilibrium return rate. The results point to the presence of two long-term cointegration vectors between MENA and developed countries, while causality direction is bidirectional. The VECM results suggest the presence of a short-term cointegration between these countries. VECM's residuals and the Wald test confirm the robustness of our model. Keywords: Financial market, Financial cointegration, Causality, VECM, MENA countries. JEL Classifications: G15, G11, G17, G1 DOI: https://doi.org/10.32479/ijefi.7146